2008
DOI: 10.1007/s00018-008-8492-5
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase a light source for the silica-based optical waveguides (spicules) in the demosponge Suberites domuncula

Abstract: Two classes of sponges (animal phylum Porifera) possess a siliceous skeleton which is composed of spicules. Studying the optical fiber-mechanical properties of large spicules from hexactinellid sponges (> 5 cm) it was demonstrated that they are effective light-collecting optical fibers. Here, we report that the demosponge Suberites domuncula is provided with a biosensor system composed of the (organic) light producing luciferase and the (inorganic) light transducing silica spicules. The light transmission feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 74 publications
2
58
0
1
Order By: Relevance
“…and A. filiformis ; figure 6). Recently, similar cases were described for the sponge Suberites domuncula and for the squid Watasenia scintillans , in which firefly-type luciferases were demonstrated to be involved in light emission [71,72] (figure 6). Luciferases could be co-opted from other genes with other functions and share high similarity with these primary genes, as was shown in the case of insect bioluminescence in which luciferases evolved from acyl-CoA ligases [39].…”
Section: Resultsmentioning
confidence: 69%
“…and A. filiformis ; figure 6). Recently, similar cases were described for the sponge Suberites domuncula and for the squid Watasenia scintillans , in which firefly-type luciferases were demonstrated to be involved in light emission [71,72] (figure 6). Luciferases could be co-opted from other genes with other functions and share high similarity with these primary genes, as was shown in the case of insect bioluminescence in which luciferases evolved from acyl-CoA ligases [39].…”
Section: Resultsmentioning
confidence: 69%
“…Following the completion of the molecular biology studies we had unequivocally demonstrated the presence of the gene encoding luciferase [25] and we also reported on the existence of a gene for the luciferin-regenerating enzyme. Furthermore, after demonstrating for the first time both the property of the demosponge spicules to act as optical waveguides and the capacity of the animals to produce light in crude extracts, we showed that the recombinant luciferase was bioactive and caused bioluminescence activity in vitro.…”
Section: Light Generating Machinery: Luciferaseluciferinmentioning
confidence: 91%
“…In order to identify the luciferase in S. domuncula our EST database was screened with the main focus on the presence of polypeptides comprising the characteristic domains for metazoan luciferase [25], e.g., the acetyl-coenzyme A (acyl-CoA) synthetase region and the luciferinbinding site residues. This database, which comprises 30000 ESTs, can be considered to cover most of the genes in sponges.…”
Section: Light Generating Machinery: Luciferaseluciferinmentioning
confidence: 99%
See 2 more Smart Citations